(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Diversity management is a relatively new management field that arose from a variety of historical and social challenges. According to (Leopold and Harris 2009), there is no commonly agreed meaning of the word "managing diversity" in the diversity management literature. To select respondents from the purposively selected NCR-Haryana-sub region ,three districts of the region , the study will employ various sampling techniques, to select respondents from selected banks and to determine sample size for each town. In this study, we aim to build on previous work on workplace diversity by conceptualizing and empirically examining the effects of various variables on organizational and employee performance in the context of workgroup working environments in order to better understand the impact of workplace diversity on organizational effectiveness.